1968
DOI: 10.2337/diab.17.6.353
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Nicotinic Acid in Acute Insulin Deficiency in the Rat

Abstract: To investigate the role of increased free fatty acid (FFA) mobilization in the hyperglycemia, ketonemia, hyperlipemia and fatty liver produced by acute insulin deficiency, nicotinic acid was used to inhibit FFA mobilization in rats given guinea pig anti-insulin serum (AIS). Effects on concentration of plasma FFA, blood glucose and betahydroxybutyric acid (BHBA), and plasma and liver lipids were studied acutely after nicotinic acid administration and during six and twenty-four hours of treatment with this compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

1969
1969
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
2
10
0
2
Order By: Relevance
“…In previous studies, nicotinic acid has been shown to both increase and decrease plasma glucose concentration in normal and diabetic humans and animals (7,(66)(67)(68)(69)(70)(71)(72)(73)(74). The reason for these discrepancies is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, nicotinic acid has been shown to both increase and decrease plasma glucose concentration in normal and diabetic humans and animals (7,(66)(67)(68)(69)(70)(71)(72)(73)(74). The reason for these discrepancies is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes 37: [28][29][30][31][32]1988 T he acute administration of either nicotinic acid (NA) or phenylisopropyladenosine (PIA), two potent antilipolytic agents, has been shown to lower elevated plasma free-fatty acid (FFA) concentrations in a rat model of non-insulin-dependent diabetes mellitus (NIDDM) (1). The fall in plasma FFA concentration was accompanied by a decrease in plasma triglyceride (TG) concentration, secondary to a reduction in very-low-density lipoprotein (VLDL)-TG secretion rate (1).…”
mentioning
confidence: 99%
“…Nicotinic acid (NA), the B group vitamin used in long-term treatment of some of the hyperlipidemic syndromes, fulfills these requirements. Acutely (within a few hours) NA lowers plasma free fatty acid levels (6-9) resulting in improved insulin action (10)(11)(12). However, during prolonged administration of NA (several days) free fatty acid levels are increased (13).…”
Section: Introductionmentioning
confidence: 99%